2017
DOI: 10.1186/s13012-017-0628-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing citation networks for dissemination and implementation research frameworks

Abstract: BackgroundA recent review of frameworks used in dissemination and implementation (D&I) science described 61 judged to be related either to dissemination, implementation, or both. The current use of these frameworks and their contributions to D&I science more broadly has yet to be reviewed. For these reasons, our objective was to determine the role of these frameworks in the development of D&I science.MethodsWe used the Web of Science™ Core Collection and Google Scholar™ to conduct a citation network analysis f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 97 publications
1
77
0
1
Order By: Relevance
“…Similarly, we found that a lack of knowledge of and familiarity with existing implementation theories, models and frameworks, along with a lack of proper training on their use, were key individual/team-level barriers to selection. These knowledge and skills barriers were not surprising given the abundance of implementation theories, models and frameworks coupled with low citation rates in the literature, indicating they are not commonly used (2,12). Our study reaffirmed this finding by demonstrating that a group of implementation researchers and practitioners with high self-rated knowledge and experience generated a list of 28 theories, models, and frameworks, which represent less than 20% of those identified in a scoping review.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Similarly, we found that a lack of knowledge of and familiarity with existing implementation theories, models and frameworks, along with a lack of proper training on their use, were key individual/team-level barriers to selection. These knowledge and skills barriers were not surprising given the abundance of implementation theories, models and frameworks coupled with low citation rates in the literature, indicating they are not commonly used (2,12). Our study reaffirmed this finding by demonstrating that a group of implementation researchers and practitioners with high self-rated knowledge and experience generated a list of 28 theories, models, and frameworks, which represent less than 20% of those identified in a scoping review.…”
Section: Discussionsupporting
confidence: 72%
“…Despite a growing interest in the appropriate selection and use of implementation theories, models and frameworks (7)(8)(9)(10)(11), it can be difficult to sift through and make sense of the various options available -especially when most are used in practice only once or with limited justification (2,12). For instance, participants in an implementation practice training course (13) reported that they struggled to identify and select suitable theories, models or frameworks to guide their work.…”
Section: Introductionmentioning
confidence: 99%
“…Forty‐six items assessed potential barriers via a 5‐point Likert scale ranging from 1 (strongly disagree) to 5 (strongly agree) (Table ). Items are aligned to the 14 domains of the theoretical domains framework (TDF), one of the most used frameworks in implementation science . The TDF is a synthesis of 33 theories and 128 key theoretical constructs related to behaviour change, designed to assess implementation barriers and inform intervention design .…”
Section: Methodsmentioning
confidence: 99%
“…Items are aligned to the 14 domains of the theoretical domains framework (TDF), one of the most used frameworks in implementation science. 17 The TDF is a synthesis of 33 theories and 128 key theoretical constructs related to behaviour change, designed to assess implementation barriers and inform intervention design. 18 Domains contain between two and four items (Table 1) and were adapted to suit the study context from previously validated quantitative TDF surveys designed for barrier assessment.…”
Section: Canteen Policy Implementation Barriersmentioning
confidence: 99%
“…The Consolidated Framework for Implementation Research (CFIR) is a determinant framework that provides a menu of constructs or determinants (potential barriers and facilitators to implementation) by which to assess and describe context [2][3]. It is among the most widely used implementation frameworks, which makes it a useful tool for reporting and referencing ndings across studies [4]. The Organizational Resource and Context Assessment (ORCA) was developed based on the Promoting Action Research into Health Services (PARiHS) framework and assesses PARiHS' three key domains of strength of evidence for a speci c EBI; the favorability of the organizational context for change; and capacities to facilitate the implementation of the EBI.…”
Section: Introductionmentioning
confidence: 99%